Philosophy and Concept of Leadership in Change Management SDM Da'wah Institute - Tamirano, Randi; Castrawijaya, Cecep (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This study discusses the philosophy and concept of leadership in HR change management in da'wah institutions. This research aims to identify and explain the philosophy and concept of leadership that can be applied in HR change management in da'wah institutions. The research method used is a literature study by collecting data from various sources such as books, journals, and articles that are relevant to the research topic. The study results show that the philosophy of leadership in HR change management in da'wah institutions should be based on Islamic values ??that prioritize fairness, integrity, simplicity, involvement, and concern for others. The concept of leadership that can be applied in changing human resource management in da'wah institutions is transformational leadership, in which leaders motivate and influence their subordinates to achieve common goals in a positive and inspiring way. In addition, participatory leadership can also be applied, where the leader builds cooperation and participation from all organization members in the decision-making process and planning strategies.